Existence of Solutions of a Nonlocal Elliptic System via Galerkin Method - Alberto Cabada; Francisco Julio S. A. Corrêa (Abstract and Applied Analysis)
By means of the Galerkin method and by using a suitable version of the Brouwer fixed-point theorem, we establish the existence of at least one positive solution of a nonlocal elliptic N-dimensional system coupled with Dirichlet boundary conditions.